Dampak Dimensi-Dimensi Pemberdayaan Pada Kinerja Anggota Tim - Ahmad Febriyanto (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
This research aims to investigate the impact of empowerment dimensions on team member performance in an organizational context. Empowerment is measured through the dimensions of autonomy, competence, participation and responsibility. The research method used was a questionnaire survey given to team members in various organizations. The collected data was analyzed using statistical techniques to identify the relationship between empowerment dimensions and team member performance. The results of this research can provide insight for managers and organizational leaders in improving team performance through optimizing empowerment dimensions.